Bacterial Endophytes Contribute to Rice Seedling Establishment Under Submergence - Ahumada, Germán Darío; Gómez-Álvarez, Eva María; Dell’Acqua, Matteo; Bertani, Iris; Venturi, Vittorio; Perata, Pierdomenico; Pucciariello, Chiara (Frontiers in Plant Science, 2022)
Flooding events caused by severe rains and poor soil drainage can interfere with plant germination and seedling establishment. Rice is one of the cereal crops that has unique germination strategies under flooding. One of these strategies is based on the fast coleoptile elongation in order to reach the water surface and re-establish the contact with the air. Microorganisms can contribute to plant health via plant growth promoters and provide protection from abiotic stresses. To characterise the community composition of the microbiome in rice germination under submergence, a 16S rRNA gene profiling meta-genomic analysis was performed of temperate japonica rice varieties Arborio and Lamone seedlings, which showed contrasting responses in terms of coleoptile length when submerged. This analysis showed a distinct microbiota composition of Arborio seeds under submergence, which are characterised by the development of a long coleoptile. To examine the potential function of microbial communities under submergence, culturable bacteria were isolated, identified and tested for plant growth-promoting activities. A subgroup of isolated bacteria showed the capacity to hydrolyse starch and produce indole-related compounds under hypoxia. Selected bacteria were inoculated in seeds to evaluate their effect on rice under submergence, showing a response that is dependent on the rice genotype. Our findings suggest that endophytic bacteria possess plant growth promoting activities that can substantially contribute to rice seedling establishment under submergence.